Deming’s System of Profound Knowledge and Continuous Improvement - Donna Daniels; Michael Kroth; Davin Carr-Chellman (Adult Education Research Conference, 2022)
The aim of this review was to conceptualize continuous and lifelong learning within Deming’s System of Profound Knowledge framework to explore individual learning processes occurring over time.
Keywords: Deming’s System of Profound Knowledge; Continuous Improvement; Profound Learning